2006
DOI: 10.1111/j.1365-2036.2006.02923.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: the adjuvant role of thymopentin on immunological response to hepatitis B virus vaccine in end‐stage renal disease

Abstract: SUMMARY BackgroundIt has been calculated that 30-40% of dialysis patients fail to produce antibodies to HBsAg antigen after vaccination towards hepatitis B virus. Several authors have reported on the benefit of thymopentin (TP5) as adjuvant to vaccine against hepatitis B virus in patients receiving regular dialysis. However, consistent information on this issue is still lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Thymopentin is a synthetic pentapeptide with activity characteristic of the thymic hormone thymopoietin and is not approved for use in the U.S. It has been used to enhance interleukin 2 production and function of macrophages (46). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymopentin is a synthetic pentapeptide with activity characteristic of the thymic hormone thymopoietin and is not approved for use in the U.S. It has been used to enhance interleukin 2 production and function of macrophages (46). …”
Section: Resultsmentioning
confidence: 99%
“…Although differences in route of administration and number of booster doses administered prevent comparison with other studies, seroprotection was reported in 88.2% of adults with diabetes who received the thymopentin adjuvant and in 100.0% of previously nonresponding hemodialysis/chronic kidney disease patients with diabetes who had received TT before vaccination. Subsequent meta-analysis of studies using thymopentin adjuvant with hepatitis B vaccine in end-stage renal disease patients (with and without diabetes) found limited benefit from the addition of thymopentin to hepatitis B schedules (46). …”
Section: Resultsmentioning
confidence: 99%
“…Fabrizi et al showed that using of higher thymopentin doses as an adjuvant can lead to an increase in seroresponse rate of HBV vaccination (13). Some other adjuvants were also investigated.…”
Section: Special Groups Needs Special Attentionmentioning
confidence: 99%
“…Most of the published systematic reviews on this subject have been performed by Fabrizi et al [31] investigating potential effects of a large number of factors on HBV vaccination in dialysis patients. For example they found no significant effects for using erythropoetin (Epo) [31] and some other adjuvants [32] on the immunogeneity of HB vaccination in kidney disease patients; while several other factors significantly associated with seroconversion have also been reported by the same authors that included use of levamisole [33] , granulocyte macrophage-colony stimulating factor [32] and thymopentin use [34] . Seroresponse of patients on maintenance hemodialysis vs peritoneal dialysis …”
Section: Discussionmentioning
confidence: 92%